The impact of revitalization treatments on biological activity of soil under afforestation on post-agricultural land - Augustyniuk-Kram, Anna; Kram, Karol J. (Studia Ecologiae et Bioethicae, 2020)
In Poland, afforestation is usually carried out on the weakest soils, excluded from agricultural use and wasteland, i.e. post-agricultural land. A characteristic feature of such habitat is poor-quality soil, relatively high content of nutrients for trees, particularly nitrogen, as well as a low level of humus. This is important for the quality of microbiological processes occurring in post-agricultural soils. Restitution of the forest in such a habitat requires the use of various revitalisation treatments for improving soil quality and increasing biological activity and soil fertility. This article presents the results of a long-term experiment on the effectiveness of various revitalisation treatments (zoo- and phytomelioration) on afforested post-agricultural lands after more than 30 years from their application in pine forests in north-western Poland. These treatments consisted of introducing additional organic matter into the soil in the form of bark and sawdust, sowing lupine and introducing soil fauna. The comparative area for afforestation on post-agricultural soils in the presented experiment was the area of forest soils, located in the same habitat, in a pine stand, at the same time. Biological activity of soil was measured with the activity of soil enzymes dehydrogenases and acid phosphatase, the biomass of microorganisms was measured and the content of total dissolved carbon and nitrogen was also determined.